3D Printing of Pharmaceutical Application: Drug Screening and Drug Delivery - Ge Gao; Minjun Ahn; Won-Woo Cho; Byoung-Soo Kim; Dong-Woo Cho (MDPI AG, 2021)
Advances in three-dimensional (3D) printing techniques and the development of tailored biomaterials have facilitated the precise fabrication of biological components and complex 3D geometrics over the past few decades. Moreover, the notable growth of 3D printing has facilitated pharmaceutical applications, enabling the development of customized drug screening and drug delivery systems for individual patients, breaking away from conventional approaches that primarily rely on transgenic animal experiments and mass production. This review provides an extensive overview of 3D printing research applied to drug screening and drug delivery systems that represent pharmaceutical applications. We classify several elements required by each application for advanced pharmaceutical techniques and briefly describe state-of-the-art 3D printing technology consisting of cells, bioinks, and printing strategies that satisfy requirements. Furthermore, we discuss the limitations of traditional approaches by providing concrete examples of drug screening (organoid, organ-on-a-chip, and tissue/organ equivalent) and drug delivery systems (oral/vaginal/rectal and transdermal/surgical drug delivery), followed by the introduction of recent pharmaceutical investigations using 3D printing-based strategies to overcome these challenges.